Neurotransmitters crosstalk and regulation in the reward circuit of subjects with behavioral addiction - Zhenlei Peng; Qiyu Jia; Junxiong Mao; Xiao Luo; Anqi Huang; Hao Zheng; Shijie Jiang; Qi Ma; Qi Ma; Chuang Ma; Qizhong Yi (Frontiers in Psychiatry)
Behavioral addictive disorders (BADs) have become a significant societal challenge over time. The central feature of BADs is the loss of control over engaging in and continuing behaviors, even when facing negative consequences. The neurobiological underpinnings of BADs primarily involve impairments in the reward circuitry, encompassing the ventral tegmental area, nucleus accumbens in the ventral striatum, and prefrontal cortex. These brain regions form networks that communicate through neurotransmitter signaling, leading to neurobiological changes in individuals with behavioral addictions. While dopamine has long been associated with the reward process, recent research highlights the role of other key neurotransmitters like serotonin, glutamate, and endorphins in BADs’ development. These neurotransmitters interact within the reward circuitry, creating potential targets for therapeutic intervention. This improved understanding of neurotransmitter systems provides a foundation for developing targeted treatments and helps clinicians select personalized therapeutic approaches.